Efektivitas Metode Pembelajaran Berbasis TBLA dengan Memanfaatkan Prior Knowledge dan Kearifan Lokal dalam Pembelajaran Bahasa Indonesia di SDS Soekarno Hatta - Ratnaningsih, Dewi; Hartono; Aprilia, Rida; Kristina, Marilin (Universitas Muhammadiyah Kotabumi, 2025)
This study examines the effectiveness of a Task-Based Language Assessment (TBLA) method integrated with students' prior knowledge and the local wisdom of Piil Pesenggiri in Indonesian language learning. The research employed the ADDIE model combined with lesson study, involving fifth-grade elementary students as subjects. Results demonstrated significant improvements in: (1) average learning outcomes (77.25, categorized as